Analisis Determinan Kejadian Stunting Pada Balita Usia 1 – 5 Tahun di Wilayah Kerja Upt Puskesmas Saripoi - elvita cintami; Erina Eka Hatini; Herlinadiyaningsih Herlinadiyaningsih (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2023)
Toddler age is a period where the process of growth and development occurs very rapidly. One of the most common nutritional problems is stunting. Stunting is one of several nutritional problems experienced by toddlers in the world. The study aims to analyze the determinants of stunting in toddlers aged 1-5 years. Research Method Quantitative data collection used a cross sectional approach. The sampling method in this study used non-probability sampling with consecutive sampling. The number of samples is 60 respondents. Based on the results of the chi square statistical test, there is a significant relationship between maternal education and the incidence of stunting (P value = 0.011); there is a significant relationship between the mother's occupation and the incidence of stunting (p value = 0.001); there is a significant relationship between the father's income factor and the incidence of stunting (P value = 0.022); and there is a significant relationship between the history of the disease and the incidence of stunting (p value = 0.017). Mother's education, mother's occupation, father's income, and history of illness influence the incidence of stunting in the Saripoi Health Center UPT Work area.